Aransemen Nyanyian Kebalai dalam Format Paduan Suara Campuran dengan Iringan Musik Etnis Rote Ndao - Agnes Emalisa (Institut Agama Kristen Negeri Kupang, 2021)
This study aims to describe the arrangement of a kebalai song in the form of a mixed choir along with ethnic Rote Ndao music accompaniment. This research use desciptive qualitative approach. The research data were obtained by means of; 1) Observation, 2) Interview (Interview), 3) Documentation. The tools used are in the form of interview guidelines, field notes, and sibelius as a presentation application. Music analysis is carried out in several stages; 1) selecting the work to be arranged, 2) processing the work (vocal arrangement and instrument arrangement), 3) orchestration and 4) presentation of the arrangement. The validity test uses triangulation sources and data collection. The results showed that the arrangements made were different from the original singing, but were still in a simple form and easy to hear with pop music styles, there was a development in vocal music both in harmony and musical style and for accompaniment there was development in rhythm, melody and alteration patterns. on a chord. The tempo used is moderate from the beginning then after the bridge there is a change in tempo. The form of presenting the kebalai song arrangement is to use sibelius. Vocals use soprano, alto, tenor and bass while the instruments used consist of one melodic instrument and three rhythmic instruments, namely Sasando, gong, drum and cymbal.